Információelmélet és marketing - Kis, Mária (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In the lat analysis the informationtheory puts the matter in another light the questionaris and those results. In analysis it is possible use arithmetic of informationtheory and those show to interesting connections , but these prove insufficient for itself. It is necessary completing the quantitative analyses of information with qualitative analyses.